Kegiatan Pelatihan Tahsin Tilawah Al-Quran Dalam Meningkatkan Kemampuan Membaca Alquran Bagi Anggota Aisyiyah Pasar 4 Bandar Khalipah - Zuliana, Zuliana; Niswa, Khairun; Rahman, Abd; Aktar, Salim (Indonesia Berdaya, 2022)
The implementation of the Qur'an Tahsin training is aimed at members of Aisyiyah Pasar 4 Bandar Khalifah who are currently not fluent in reading the Qur'an properly and correctly, even though they are adults. However, it is never too late to learn. This Al-Qur'an tahsin training activity aims to be able to improve understanding in reading the Qur'an and understand the methods in reading the Qur'an properly and correctly. The method provided is in the form of short material and tips for reading with the rules of recitation. Furthermore, significant results have been obtained for Aisyiyah members in understanding and practicing the reading of the Qur'an. This shows that basically, the level of success of this training is achieved if it is learned and practiced as well as directly, so it takes consistency in reading the Qur'an on a daily basis which aims to maintain the rules of recitation and pronunciation so that they are better and of higher quality